2022
DOI: 10.3390/su14148326
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Parents’ Awareness of Children’ Education Investment: A Systematic Review

Abstract: Parents’ awareness of the importance of education greatly influences decision-making on educational extensions for children. Because more and more parents are aware of the importance of education in supporting the survival of children in the future, parents will be more aware of expanding education to a higher level for the benefit of the children, the environment, and the future. The objective of this study is to identify the factors that influence parents’ awareness in investment decision-making for children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…This finding is in line with the results of past research whereby parents must be able to know the talents and interests of their children (Bai et al, 2020;Chung & Lee, 2017;Hargreaves, 2021;Nakagawa et al, 2021;Sellami et al, 2019). Parents should also adjust courses and educational institutions that can increase their children's potential and not impose their will on the programme to be pursued (Wati & Sahid, 2022).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is in line with the results of past research whereby parents must be able to know the talents and interests of their children (Bai et al, 2020;Chung & Lee, 2017;Hargreaves, 2021;Nakagawa et al, 2021;Sellami et al, 2019). Parents should also adjust courses and educational institutions that can increase their children's potential and not impose their will on the programme to be pursued (Wati & Sahid, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, past studies have demonstrated the instability of parents' decisions to invest in education at a higher education level, as indicated by the data of gross participatory figures (APK) over the past 5 years (2017-2021) in 2017 (112.72%), 2018 (113.24%), 2019 (109.47%), 2020 (109.01%) and 2021 (115.26%) due to several influencing factors, one of which includes the family factor. This is inversely proportional to the results of research, which states that the family is the main determinant of decisions at the last level of education that must be taken, because one of the factors that affect education investment is internal factors derived from parental decisions (educational planning, educational process, quality of education and competitiveness) in supporting the maximum education (Wati & Sahid, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the results of education investment or the rate of return they will get are not always in the form of a sum of money and interest adjusted to the amount of money they have invested at the beginning, but the returns they can receive from the results of this investment can be in the form of funds derived from children's income when they have got a job or not money such as developing their potential. This is following the results of research which states that investment in education provides a higher rate of return than other types of investment because education investment can offer better value in increasing individual productivity in the future (Becker, 1993;McConnell et al, 2016;Psacharopoulos & Patrinos, 2018;Wati & Sahid, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…In recent years, the deep involvement of parents in their children's education has become a social phenomenon that has attracted much attention, and parents' educational involvement behaviour has become a major issue that needs to be studied in depth by academics (Heckman & Letkiewicz, 2021;Wati & Sahid, 2022). Family education is the foundation of all education and has a significant impact on educational justice and the quality of future citizens (Molla & Pham, 2019;Ocampo-González, 2019).…”
Section: Introductionmentioning
confidence: 99%